On the structure of boron trifluoride in liquid and supercritical phase investigated with neutron diffraction - McLain, SE; Siewenie, J; Benmore, C; Turner, J (2003)
Neutron diffraction analysis was used to study the structure of boron trifluoride in liquid and supercritical phase. Liquid BF3 displays order only in the first coordination sphere around the average molecule and there was no intermediate range order. The angular analysis using reverse Monte Carlo modeling showed that the dominant structural motif in the solid state was partially retained in both the liquid and supercritical phase.